2019
DOI: 10.2478/afepuc-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Mobility in Women with Sedentary Job

Abstract: Summary The aim of the paper is to provide insight into the spine mobility of a selected group of women. The task was to diagnose and evaluate spinal mobility in women aged 25 to 30, who are dominated by a sedentary way in workplace but also outside the work environment. Spinalmouse® technology was used for diagnostic purposes, which records the shape and mobility of the spine in the sagittal and frontal plane. Tests were performed in the sagittal and frontal plane of the baseline. The sm® software evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The studies on spinal mobility in different sexs have produced mixed results. While some studies have found no significant differences in spine mobility between sexs [13][14][15], other studies suggest that sex differences in spinal mobility may be influenced by factors such as job type, disease, and spinal level. Our findings indicate significant differences in postural deviations between men and women, with a stronger correlation observed in women.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The studies on spinal mobility in different sexs have produced mixed results. While some studies have found no significant differences in spine mobility between sexs [13][14][15], other studies suggest that sex differences in spinal mobility may be influenced by factors such as job type, disease, and spinal level. Our findings indicate significant differences in postural deviations between men and women, with a stronger correlation observed in women.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, researchers observed that postural disorders significantly differed in children living in urban and suburban environments [11,12]. Similar studies have reported conflicting evidence regarding urban-rural differences in the influence of living area on spine ROM [13][14][15]. Finally, age and sex may also impact students' posture.…”
Section: Preprintsmentioning
confidence: 99%
“…Although the effect of diaphragmatic, exhalation, and inspiratory breathing exercises on spinal mobility (Kang et al, 2018;Lenková and Vasilišinová, 2019) and postural stability (Tajali et al, 2022;Stephens et al, 2017;Armstrong et al, 2018;D'souza et al, 2021;Farzami and Anbarian, 2020;Roth et al, 2021;Ferraro et al, 2020) has been investigated, there are no studies dealing with their recovery following by prolonged sitting at the workplace. People exposed to repetitive, prolonged sitting at their work are prone of back problems, especially in late middle-age.…”
Section: Clinicalmentioning
confidence: 99%
“…While the first one is related to a decrease in the spine’s range of motion, the second one is related to a decrease in spine velocity ( Hamaoui et al, 2004 ). Assessment using the spinal mouse suggests that spinal mobility may be impaired as a result of fatigue induced by prolonged sitting ( Lenková and Vasilišinová, 2019 ). Decreased spinal mobility leads to abnormal lumbar vertebrae movement as a compensatory mechanism ( Sung et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of diaphragmatic, exhalation, and inspiratory breathing exercises on spinal mobility ( Kang et al, 2018 ; Lenková and Vasilišinová, 2019 ) and postural stability ( Tajali et al, 2022 ; Stephens et al, 2017 ; Armstrong et al, 2018 ; D’souza et al, 2021 ; Farzami and Anbarian, 2020 ; Roth et al, 2021 ; Ferraro et al, 2020 ) has been investigated, there are no studies dealing with their recovery following by prolonged sitting at the workplace. People exposed to repetitive, prolonged sitting at their work are prone of back problems, especially in late middle-age.…”
Section: Introductionmentioning
confidence: 99%